Analisa Etos Kerja Perempuan dalam Menopang Kemandirian Ekonomi Keluarga di Desa Kemiri, Kecamatan Puspo Pasuruan: Studi Pendekatan Asset Based Community Development (Abcd) - Siti Alviyaning Tiyas; Sukamto Sukamto; Aslikhah Aslikhah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze women’s work ethic in supporting family economic independence through the Asset Based Community Development (ABCD) approach in Kemiri Village, Puspo District, Pasuruan Regency. This research employed a qualitative approach with a descriptive-explanatory type. Data were collected through observation, in-depth interviews, and documentation involving women working in agriculture, trading, livestock farming, handicrafts, and education sectors. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using the ABCD perspective. The findings revealed that women possess a strong work ethic reflected in discipline, responsibility, perseverance, and consistency in carrying out economic activities. Women were also able to utilize local assets such as individual skills, agricultural land, livestock, and social support from the community to sustain family economic activities. The utilization of these local assets indicates the implementation of ABCD principles within community life. This study concludes that the integration of women’s work ethic and local asset utilization plays an important role in strengthening family economic independence and the economic resilience of rural communities.